2022
DOI: 10.3390/pathogens11111337
|View full text |Cite
|
Sign up to set email alerts
|

Is Hepatitis E Virus a Neglected or Emerging Pathogen in Egypt?

Abstract: Though Egypt ranks among the top countries for viral hepatitis and death-related liver disease, Hepatitis E virus (HEV) is a neglected disease. Living in villages and rural communities with low sanitation, use of underground well water and contact with animals are the main risk factors for HEV infection. Domestic animals, especially ruminants and their edible products, are one source of infection. Contamination of water by either human or animal stools is the main route of infection. In addition, HEV either al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…The Hepatitis E distinctive zone is still limited to Egypt, as the infection pattern differs from other world regions [ 61 ]. In this zone, the prevalence is higher (60–80% seropositivity), especially in the first decade of life [ 62 ], and most young people develop HEV IgG antibodies with a seroprevalence resembling that of HAV. Interestingly, the incidence is lower among pregnant women, and the infection is either asymptomatic or very mild with no fulminant course.…”
Section: Epidemiologymentioning
confidence: 99%
“…The Hepatitis E distinctive zone is still limited to Egypt, as the infection pattern differs from other world regions [ 61 ]. In this zone, the prevalence is higher (60–80% seropositivity), especially in the first decade of life [ 62 ], and most young people develop HEV IgG antibodies with a seroprevalence resembling that of HAV. Interestingly, the incidence is lower among pregnant women, and the infection is either asymptomatic or very mild with no fulminant course.…”
Section: Epidemiologymentioning
confidence: 99%
“…HEV contamination has been detected in dry-cured pork products and pork liver sausages (consisting of raw liver) in European countries with heavy pork diets. Contamination of water bodies with ground water or sewage from pig farms has also been shown to spread HEV-3 and HEV-4 [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the last two decades revealed that HEV infection is endemic in Egypt [ 18 , 19 ]. A high rate of anti-HEV IgG seroprevalence is reported in rural communities, especially among villagers and pregnant women [ 18 , 19 , 20 , 21 ]. HEV-infected patients were either asymptomatic or developed the acute self-limiting disease [ 20 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high rate of anti-HEV IgG seroprevalence is reported in rural communities, especially among villagers and pregnant women [ 18 , 19 , 20 , 21 ]. HEV-infected patients were either asymptomatic or developed the acute self-limiting disease [ 20 , 22 , 23 , 24 ]. The actual prevalence of HEV infection in Egypt is not known due to either silent infection and/or the infection not being documented or monitored.…”
Section: Introductionmentioning
confidence: 99%